A CONCEPTUAL REVIEW OF THE TALENT MANAGEMENT AND EMPLOYEE RETENTION IN BANKING INDUSTRY - Akanda, Mohammad Helal Uddin; Bhuiyan, Abul Bashar; Kumarasamy, Mokana Muthu; Karuppannan, Gunasegaran (International Journal of Business and Management Future, 2021)
The value of talent workers, talent management and talent retention has increased in the increasing economic circumstances of the world. Talented and devoted employees are often an integral part of every company. Smart, sophisticated, digitally literate, internationally astute and operationally agile businessmen are considered talented individuals. Talent management means that organisations have access to strategic planning with the best candidates with relevant expertise placed in the right place. Therefore, the aim of this study is to develop a conceptual model that explain the relationship between talent management and employee retention. The study will be used to accumulate empirical literature by the name of talent management and talent retention in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST, etc. The review findings of the study shown that any success or loss of a company mostly depends on the activities and survival of talented employees. The study also found that the retention of employees is one of the challenges that many public and private organisations face, has become an even greater challenge facing human resources professionals because there is a luxury of choice for talented candidates in the global job skills market. At the same time, there is a lack of research emphasizing only on banking industry. The proposed conceptual model depicts the significant effect of working environment and other dimensions of talent management and its effect on employee retention in banking industry.